The Impact of Digital Trade on the Export Competitiveness of Enterprises—An Empirical Analysis Based on Listed Companies in the Yangtze River Economic Belt - Lifan Yang; Weixin Yang; Longjiang Nan; Yuxun Gu (Systems)
With the in-depth development of globalization and informatization, digital trade, as an emerging form of trade, is gradually reshaping the global economic landscape and becoming a new engine for driving economic growth. Among them, the impact of digital trade on the export competitiveness of enterprises in developing countries has become a common concern in academia. To reveal the causal relationship between the development of digital trade and the enhancement of export competitiveness in developing countries, this paper first constructs a theoretical model based on product quality heterogeneity and analyzes the impact of digital trade on the export competitiveness of enterprises on the basis of achieving supply and demand equilibrium; then, this paper constructs a comprehensive index system for measuring digital trade and enterprise export competitiveness, and establishes an empirical analysis model; on this basis, this paper uses the data of listed companies in the A-share market in the Yangtze River Economic Belt area from 2011 to 2021 for empirical analysis. The results of the empirical analysis show that for every one-unit increase in the level of digital trade development in the region, there will be a positive impact of 0.9041 units on the export competitiveness of enterprises. After a series of robustness tests and endogeneity analyses, the above empirical results are confirmed to be robust and reliable. Furthermore, this paper conducts a heterogeneity analysis and finally puts forward corresponding policy recommendations based on the above theoretical and empirical research results.